2019
DOI: 10.1158/0008-5472.can-18-0717
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PP2A and Inhibition of mTOR Synergistically Reduce MYC Signaling and Decrease Tumor Growth in Pancreatic Ductal Adenocarcinoma

Abstract: In cancer, kinases are often activated and phosphatases suppressed, leading to aberrant activation of signaling pathways driving cellular proliferation, survival, and therapeutic resistance. Although pancreatic ductal adenocarcinoma (PDA) has historically been refractory to kinase inhibition, therapeutic activation of phosphatases is emerging as a promising strategy to restore balance to these hyperactive signaling cascades. In the current study, we hypothesized that phosphatase activation combined with kinase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 47 publications
6
62
0
1
Order By: Relevance
“…Recently, Kauko et al [111] demonstrated that knockdown of PP2A contributes to kinase inhibitor resistance, in part due to the induction of high MYC levels. Consistent with these studies, we recently demonstrated that select kinase inhibitors can function synergistically with SMAPs in breast and pancreatic cancer cells [140]. Specifically, the combination of mammalian target of rapamycin (mTOR) inhibitors and SMAPs synergistically reduced MYC levels beyond the capabilities of either single agent and potently induced cell death.…”
Section: Direct Pp2a Activationsupporting
confidence: 53%
See 1 more Smart Citation
“…Recently, Kauko et al [111] demonstrated that knockdown of PP2A contributes to kinase inhibitor resistance, in part due to the induction of high MYC levels. Consistent with these studies, we recently demonstrated that select kinase inhibitors can function synergistically with SMAPs in breast and pancreatic cancer cells [140]. Specifically, the combination of mammalian target of rapamycin (mTOR) inhibitors and SMAPs synergistically reduced MYC levels beyond the capabilities of either single agent and potently induced cell death.…”
Section: Direct Pp2a Activationsupporting
confidence: 53%
“…Using binding assays and photoaffinity labeling, Sangodkar et al [139] demonstrated that SMAPs bind directly to the PP2A-Aα subunit, causing a conformational change that alleviates negative inhibition and leads to PP2A activation. Treatment with SMAPs reduces tumor growth and proliferation in pancreatic, lung, and castrationresistant prostate cancer, in vivo and in vitro [111,139,140]. These results are associated with attenuated oncogenic signaling, with significant decreases in active ERK, SRC, CDK, and MYC.…”
Section: Direct Pp2a Activationmentioning
confidence: 94%
“…In particular, dephosphorylation of AKT, ERK, and MYC is carried out by PP2A, which promotes the degradation of MYC via the proteasome (66,67). We hypothesized that using a new small-molecule activator of PP2A (SMAP) (68,69), DT1154, may decrease S62-MYC phosphorylation while simultaneously downregulating other oncogenic pathways, providing therapeutic benefit in the MYC;NeuNT model. We treated tumor-bearing MYC;NeuNT mice with the SMAP, DT1154 (100 mg/ kg b.i.d.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the Dupre et al [5], Lemmonier et al [9] and Dupre et al [139] completely ignored published works that contradicted their work and did not provide any reasons to the readers and Scientific Researchers who are trying to decipher who is/are telling the truth and whether to spend resources in man hours to try to repeat their published works that are at best misleading and at worse dishonest. The idea that a form of PP-2A could undergo marked inhibition during resumption of meiosis is not compatible with the known function of PP-2A as a key controller of cell transformation and as tumor suppressor [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100].…”
Section: Role Of Pp-2a In the Control Of Mitosismentioning
confidence: 99%
“…One or more form(s) of PP-2A in the cell has/have low basal activity upon entry into mitosis and becomes moderately activated prior to and exit of mitosis. As countless studies have shown, logically, extensive inhibition of PP2A would lead to cell transformation and tumorigenesis[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100].The following model for the role of PP-1 and PP-2A in the control of mitosis that does not rest upon the conclusions of Mochida et al[1] and Gharbi-Ayashi et al[2] are a lot more realistic. The model takes in account the works of Mayer-Jackel et al[24,25], Hutchins et al[26], Peng et al[101,102], Margolis et al[27,115,116], Forrester et al[28], Wu et al[117], Tung et al[110,111,156], Puntoni and Villa-Moruzzi[152,153], Dohadwala et al[161], Kwon et al[162], Lamb et al[165], Brautigan et al[166], Fernandez et al[167], and Li et al[160], Model for the role of PP-2A in the control of meiosis.Role of PP-2A in the control of meiosis in Xenopus oocytes.…”
mentioning
confidence: 99%